Effects of volatiles on properties of char during sequential pyrolysis of PET and cellulose. (April 2022) - Li, Chao; Sun, Yifan; Li, Qingyang; Zhang, Lijun; Zhang, Shu; Wang, Huaisheng; Hu, Guangzhi; Hu, Xun
Abstract: Interaction of the volatiles in co-pyrolysis of plastics and biomass is known to affect properties of pyrolysis products. Nevertheless, in co-pyrolysis, except the interaction between the volatiles, the volatiles could also interact with the char of same or different origin. Thus, understanding the specific effects of the volatiles of plastics/biomass on the evolution of the char from biomass/plastics is difficult. Hence, the investigation of the sequential pyrolysis of cellulose and polyethylene terephthalate (PET) at 600 °C was to explore the specific influences of volatiles from cellulose/PET in upper bed on the property of the char from PET/cellulose in lower bed. During sequential pyrolysis with cellulose in upper bed, the cellulose-derived oxygen-rich radicals promoted the cracking of the organic component on the PET-derived char, which significantly reduced the char yield while promoted the formation of heavy organics products and reduced hydrophobicity of the PET-derived char. Additionally, the cellulose-derived volatiles (e.g. ketones and aldehydes) involved in the secondary polymerization reactions with the volatiles from PET, forming more phenolics. PET-derived hydrocarbon-rich molecules did not promote charring reactions of the cellulose-derived char but increased hydrophobicity of the cellulose-char. Moreover, the varied interaction of the volatiles also significantly impacted thermal stability of the functional groups of char. Graphical abstract: Image 1